2012
DOI: 10.1590/s1676-06032012000400007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on growth of the threatened annual fish Austrolebias nigrofasciatus Costa & Cheffe 2001

Abstract: This study evaluated the effect of temperature on growth of Austrolebias nigrofasciatus, an endemic and threatened annual killifish species of the Patos-Mirim lagoon system in Southern Brazil. In order to verify the effect of temperature on initial growth of A. nigrofasciatus, eggs stored in the laboratory were hatched and juveniles reared for eight weeks at 16 and 22 ºC. The standard length of newly hatched fishes was 4.67 ± 0.25 mm and after eight weeks they reached 23.68 ± 3.73 and 22.68 ± 5.36 mm, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Both species studied attain sexual maturity at a body size of 18–21 mm at the age of c . 8 weeks (Arenzon et al , ; Volcan et al , ), though the sexes can be distinguished in larger juveniles, especially in C. fulgens .…”
Section: Discussionmentioning
confidence: 93%
“…Both species studied attain sexual maturity at a body size of 18–21 mm at the age of c . 8 weeks (Arenzon et al , ; Volcan et al , ), though the sexes can be distinguished in larger juveniles, especially in C. fulgens .…”
Section: Discussionmentioning
confidence: 93%
“…Studies involving the management of annual fish eggs have used various incubation media, such as water (Arenzon et al, 2002;Tingaud-Sequeira et al, 2009;Blažek et al, 2013) and Yamamoto's solution (Wourms, 1972;Podrabsky, 1999;Arezo et al, 2007;Blažek et al, 2013) for maintenance in the laboratory, as well as damp media wherein the eggs are in contact with the air in a moist chamber (Arenzon et al, 2002;Tingaud-Sequeira et al, 2009;Volcan et al, 2012;Blažek et al, 2013). Only a few studies, however, have compared the survival and development pattern of embryos in these media (Podrabsky, 1999;Arenzon et al, 2002;Blažek et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Our field data are consistent with laboratory studies that have reported earlier sexual maturity and more rapid growth at higher temperature for Austrolebias spp. (Volcan et al., ). However, the positive relationship between water temperature and juvenile development is reversed when temperatures exceed an optimum of 21–24°C (Fonseca et al., ), and high ambient temperatures during juvenile growth comes at the cost of shorter lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory studies have demonstrated that annual fishes are sensitive to temperature (Fonseca, Volcan, Sampaio, Romano, & Robaldo, 2013;Volcan et al, 2012). Austrolebias adloffii, a related species from the same region, exhibited a decreased growth rate and shorter lifespan when a natural decrease in water temperature fluctuation was interrupted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation